Prediagnostic body fat and risk of death from amyotrophic lateral sclerosis: the EPIC cohort. - Gallo, V; Wark, P; Jenab, M; Pearce, N; Brayne, C; Vermeulen, R; Andersen, P; Hallmans, G; Kyrozis, A; Vanacore, N; Vahdaninia, M; Grote, V; et al. (2013)
OBJECTIVES: The aim of this study was to investigate for the first time the association between body fat and risk of amyotrophic lateral sclerosis (ALS) with an appropriate prospective study design. METHODS: The EPIC (European Prospective Investigation into Cancer and Nutrition) study included 518,108 individuals recruited from the general population across 10 Western European countries. At recruitment, information on lifestyle was collected and anthropometric characteristics were measured. Cox hazard models were fitted to investigate the associations between anthropometric measures and ALS mortality. RESULTS: Two hundred twenty-two ALS deaths (79 men and 143 women) occurred during the follow-up period (mean follow-up = 13 years). There was a statistically significant interaction between categories of body mass index and sex regarding ALS risk (p = 0.009): in men, a significant linear decrease of risk per unit of body mass index was observed (hazard ratio = 0.93, 95% confidence interval 0.86-0.99 per kg/m(2)); among women, the risk was more than 3-fold increased for underweight compared with normal-weight women. Among women, a significant risk reduction increasing the waist/hip ratio was also evident: women in the top quartile had less than half the risk of ALS compared with those in the bottom quartile (hazard ratio = 0.48, 95% confidence interval 0.25-0.93) with a borderline significant p value for trend across quartiles (p = 0.056). CONCLUSION: Increased prediagnostic body fat is associated with a decreased risk of ALS mortality.